Home visits in phenylketonuria: a 12-month longitudinal study - Gökmen-Özel, Hülya; Büyüktuncer, Zehra; Köksal, Gülden; Kalkanoğlu-Sivri, H. Serap; Coşkun, Turgay (The Turkish Journal of Pediatrics, 2011)
This study aimed to evaluate the effect of dietary education given to the caregivers of children with phenylketonuria (PKU) in their home environment on children's blood phenylalanine (Phe) levels. Thirty-six children with PKU, aged 2-12 years, were recruited. Each caregiver was visited on three separate occasions and given a detailed dietary education. Fasting morning skin puncture blood samples were collected on Newborn Screening Blood Test filter paper for Phe analysis at baseline and 1, 4, 12, 24, and 48 weeks after the home visits. The mean baseline blood Phe level (365 +/- 232 micromol/L) significantly decreased with home visits at the 1st week (314 +/- 226 micromol/L) (p < 0.05). Four weeks after the home visits, the median blood Phe level was still lower than baseline, but the difference was not statistically significant (p > 0.05). The mean blood Phe levels significantly increased at the end of the 12th, 24th and 48th weeks (329 +/- 230 micromol/L; 447 +/- 189 micromol/L and 486 +/- 261 micromol/L, respectively) (p < 0.05). A well-controlled blood Phe level can be achieved with intense, regular and continuing education programs, which include regular home visits.